Children's rights in a modern school - experiences of pedagogy students - Wiesława Walc (Maria Curie-Skłodowska University, Lublin, Poland, 2020)
Despite the ratification of the Convention on the Rights of the Child by Poland, as well as the presence of a number of provisions concerning them in the documents regulating the functioning of the education system in our country, school reality leaves much to be desired in the context of realizing the rights of children. A certain picture of this issue is provided by the research presented in the article. The survey was conducted among students of pedagogy at the University of Rzeszów, using the author's questionnaire. The surveyed students were optimistic about the implementation of children's rights in Polish schools, considering them to be generally implemented. They expressed their conviction that Polish children are guaranteed the right to learning and to education. In our country, the principle of universality and free of charge of teaching, equality in access to education is respected, as well as the right to recognize and preserve the national identity of students during schooling. On the other hand, the right to express opinions, to respect the child's own views was more often considered to be unrealized than realized, while the right to free expression and information was not much more often implemented than unrealized. As quite positive, students' experiences related to their rights as pupils can be assessed in the past. All of the rights presented to them were more often considered to be implemented than as unrealized. However, they gave examples of breaking their student rights (in the past). The perpetrators in such situations were usually teachers. The schools that the current students of pedagogy used to attend in the past played a rather small role in their education regarding children's rights. From the research, the picture of the school emerges, in which children's rights are violated by the persons appointed to perform them - teachers, and the right to express one's own opinion and respect for his views is the most often infringed and at the same time the most desirable good.